The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1111/jasp.12577
|View full text |Cite
|
Sign up to set email alerts
|

A confirmatory study of the relations between workplace sexism, sense of belonging, mental health, and job satisfaction among women in male‐dominated industries

Abstract: The present study investigated the mediating role of sense of belonging in the relations between workplace sexism and (a) mental health and (b) job satisfaction. Participants were 190 women from a large Australian trade union that represented mainly male‐dominated jobs. They completed an online survey that contained measures of sexism, sense of belonging in the industry, mental health, and job satisfaction. As predicted, sense of belonging mediated the associations between organizational sexism and both mental… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 62 publications
1
26
0
Order By: Relevance
“…The present findings indicate that this may not only be the case for concealing a concealable stigmatized identity, but also for self-group distancing among stigmatized groups more generally. In addition, recent cross-sectional research among women in male-dominated industries showed that feeling a need to reduce femininity at work (e.g., when experiencing sexism at work) was related to lower mental health and job satisfaction (Rubin et al, 2019). Future research still has to examine whether—despite these short run negative costs—distancing may in the longer run indeed enable individual mobility in the organization.…”
Section: Discussionmentioning
confidence: 99%
“…The present findings indicate that this may not only be the case for concealing a concealable stigmatized identity, but also for self-group distancing among stigmatized groups more generally. In addition, recent cross-sectional research among women in male-dominated industries showed that feeling a need to reduce femininity at work (e.g., when experiencing sexism at work) was related to lower mental health and job satisfaction (Rubin et al, 2019). Future research still has to examine whether—despite these short run negative costs—distancing may in the longer run indeed enable individual mobility in the organization.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, social identification buffered (reduced) the effects of social class on depressive symptoms. Critically, however, subsequent attempts to replicate this effect have not been successful, possibly due to measurement issues (Evans, 2019;McGuffog, 2018;Rubin, Paolini, Subašić, & Giacomini, 2019). Additionally, Iyer, Jetten, Tsivrikos, Postmes, and Haslam (2009) found that identifying as a student predicted students' greater wellbeing, but that working-class students were less likely to identify as a student or to see the student identity as being compatible with their social class identity.…”
Section: Social Class Social Integration and Mental Healthmentioning
confidence: 99%
“…Ostracism creates a context of social isolation in such a way that peers subtly deplete the victim's sense of belonging (Ferris et al 2017). We agree that a sense of belonging is critical for one's psychological health (Rubin et al 2019), negatively affecting the attitudinal outcomes such as job satisfaction, a tendency to quit, or psychological withdrawal. However, we speculate that the need to belong may be less crucial for actual performance (e.g., creative performance and job performance).…”
Section: Theoretical Implicationsmentioning
confidence: 94%